Multiproxy analysis of a Lateglacial-Holocene sedimentary section in the Fuegian steppe (northern Tierra del Fuego, Argentina): Implications for coastal landscape evolution in relation to climatic variability and sea-level fluctuations - Candel, María Soledad; Díaz, Pablo Esteban; Borromei, Ana María; Fernández, Marilén; Montes, Alejandro; Santiago, Fernando Carlos (Palaeogeography, palaeoclimatology, palaeoecology, 2020)
We report the sedimentology, palynology, geochemistry, and diatom assemblages of a well-dated succession at Laguna Las Vueltas (LV) on the Atlantic coast of the Fuegian steppe in southern Argentina. The multiproxy analysis offers a unique opportunity to study the evolution of this coastal landscape in relation to past sea level and climate changes in the southern high latitudes. After ca. 19,000 cal yr BP, the sediments were subjected to subaerial exposure and oxidation linked to a low sea level. The Sr/Ba ratio (a paleosalinity geochemical parameter) indicates variations in the water body level, and diatoms imply the existence of an ephemeral and brackish-freshwater body subject to desiccation under arid conditions. Between ca. 11,600 and 8500 cal yr BP, a shrubby steppe vegetation, mainly composed of Asteraceae subf. Asteroideae, spread over the coastal area associated with a shallow freshwater body and the deposition of fine-grained sediments in low-energy environments, all indicative of low effective moisture and warm climate conditions. Between ca. 8500 and 8100 cal yr BP, salt carpet vegetation, dominated by Chenopodiaceae, developed around a coastal lagoon in response to the Holocene marine transgression. The record of dinocysts and geochemical data indicate marine influence at this time. Between ca. 8100 and 7000 cal yr BP, salt marshes colonized the coastal area. A coastal lagoon with a more restricted connection to the sea and minor freshwater input are inferred, linked to the beginning of a regressive phase. After ca. 7000 cal yr BP, grassland vegetation and an open shrub stratum developed along with a shallow lake (pan) that was disconnected from the sea, following a fall in the sea level and regression. Fluctuations in the water level of the pan and changes in the physical-chemical conditions, as indicated by fluctuations in Mn/Fe, Ti/Ca, Rb/Sr, Ca, TIC and TOC, suggest abrupt events of desiccation and flooding. Between ca. 4500 and 2000 cal yr BP a drier phase is indicated by changes in vegetation, algal content and geochemistry of the pan. A grassland vegetation and a shallow lake with seasonal water level variations characterized the last 2000 years. Our results from LLV area match well with Andean forest fluctuations and regional climatic conditions recorded from Tierra del Fuego and Chilean southwest. •Palaeoenvironmental reconstruction for the Atlantic coast during the last 19,000 yr.•Multiproxy data provide evidences for the Fuegian coastal landscape variations.•A seawater flooding event was identified at the Las Vueltas site